Public-private Errors and Stranger-friend Errors: Revealing Sexuality Education Strategy Based on Islamic Value of Intellectually Disabled Students in Batam City of Riau Islands Province - Muna Erawati; Alif Muhammad Zakaria; Lilik Sriyanti (Psikis : Jurnal Psikologi Islami, 2025)
This research aimed to reveal various experiences, strategies, and obstacles to sexuality education for intellectually disabled students in Special Needs Schools (Sekolah Luar Biasa or SLB) and Islamic Elementary Schools (Madrasah Ibtidaiyah or MI). A qualitative descriptive method was applied. Interviews, observations, focused group discussions, and documentation were used to gather information. Principals, teachers, students, and parents from SLB and MI in Batam City, Riau Islands Province, participated in this study. Data validation was conducted using triangulation sources and techniques. Thematic analysis was used to identify, analyze, and interpret data. The results found that: first, sexuality education for students with intellectual disabilities was challenging, and teachers still encountered difficulties. Intellectual limitations caused students to experience what are called public-private errors and friend-stranger errors, which resulted in inappropriate expressions (activities) of sexuality in private vs. public spaces and difficulty differentiating between familiar vs. stranger people. Even though the teachers had long experience with special needs students and were prepared with various methods and techniques to handle them, they were still constantly looking for ways to adapt to the various conditions of students. Second, the teachers reported some obstacles, such as student characteristics, low parental involvement, and low local governmental support and policies on this issue. Third, the strategies of sexuality education for Muslim students were implemented by integrating religious teaching and values into various methods, techniques, and media.